POTRET EVALUASI PROGRAM BIMBINGAN DAN KONSELING DI SEKOLAH MENENGAH ATAS - Evi Winingsih (Universitas PGRI Madiun, 2021)
Evaluation of guidance and counseling services should ideally be conducted periodically and continuously. Appropriate evaluation procedures will provide many benefits for teachers Guidance and counseling. Evaluation gives teacher guidance and counseling feedback to develop and improve programs. Evaluations also provide information to leaders about student development and improvement efforts. Proper evaluation results will help the counselor in achieving the goals of guidance and counseling services. This study aims to determine how the evaluation process is in high school. The research method uses a descriptive qualitative approach. Data collection techniques are interviews and observation. The sampling technique was carried out through a nonprobability sampling procedure. The results of this study indicate diversity in the evaluation process carried out by high schools. There are 6 (six) types of evaluations conducted by guidance and counseling teachers in high schools. The results of the study also illustrate the evaluation techniques and the purpose of schools conducting evaluations. We hope that the results of this study can provide information to improve the quality of evaluation in the Guidance and Counseling services in Indonesia.